CLOUD COMPUTING AND SECURITY OF INFORMATION ASSETS - Miloslav Macháček (European Scientific Journal, ESJ, 2014)
This paper deals with cloud computing technology and the protection of information assets in the company. The tools and system for safety management of information assets is presented in the paper. The system design contains a detailed methodology. The use of this methodology will enable effective decision making. Many organizations and commercial companies do not know their assets and do not know they are the most valuable asset you own. Assets have huge value for organization or company. Security and protection of information assets can be divided into two basic groups: Protection against damage or loss due to natural disaster, equipment failure or human error. The goal is not alienate or destroy data. Protection against damage or loss inside in the Company's operations. Deliberately damage HW or SW, illegally obtain, degrade or alter the information is the aim. Information security management system (ISMS) deals with access to information security management. ISMS is a summary of the measures, policies, rules, uses standards and others. Companies take decisions on the use of cloud computing technologies more and more often nowadays. Unfortunately, companies do not know the risks and opportunities of this technology.